The Likelihood of Preventing Respiratory Exacerbations in Children and Adolescents with either Chronic Suppurative Lung Disease or Bronchiectasis - O’Grady, Kerry-Ann F; Grimwood, Keith (Frontiers in Pediatrics, 2017)
Chronic suppurative lung disease (CSLD) and bronchiectasis in children and adolescents are important causes of respiratory morbidity and reduced quality of life (QoL), also leading to subsequent premature death during adulthood. Acute respiratory exacerbations in pediatric CSLD and bronchiectasis are important markers of disease control clinically, given that they impact upon QoL and increase health-care-associated costs and can adversely affect future lung functioning. Preventing exacerbations in this population is, therefore, likely to have significant individual, familial, societal, and health-sector benefits. In this review, we focus on therapeutic interventions, such as drugs (antibiotics, mucolytics, hyperosmolar agents, bronchodilators, corticosteroids, non-steroidal anti-inflammatory agents), vaccines and physiotherapy, and care-planning, such as post-hospitalization management and health promotion strategies, including exercise, diet, and reducing exposure to environmental toxicants. The review identified a conspicuous lack of moderate or high-quality evidence for preventing respiratory exacerbations in children and adolescents with CSLD or bronchiectasis. Given the short- and long-term impact of exacerbations upon individuals, their families, and society as a whole, large studies addressing interventions at the primary and tertiary prevention phases are required. This research must include children and adolescents in both developing and developed countries and address long-term health outcomes.